2020
DOI: 10.1038/s41598-020-75429-3
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of the proteins related to cigarette smoke-induced cardiac hypertrophy in spontaneously hypertensive rats

Abstract: Smoking increases the risk of cardiovascular diseases. The present study was designed to determine the effects of 2-month exposure to cigarette smoke (CS) on proteins in the left ventricles of spontaneously hypertensive rats (SHR) and to identify the molecular targets associated with the pathogenesis/progression of CS-induced cardiac hypertrophy. SHR and Wistar Kyoto rats (WKY) were exposed to CS at low (2 puffs/min for 40 min) or high dose (2 puffs/min for 120 min), 5 days a week for 2 months. Using the two-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Adult SHR is an ideal animal model of compensatory LVH, as supported by increased left ventricle relative mass, elevated left ventricular end-systolic pressure in combined with greater + dp/dt max in SHR. As expected, more DEPs were found in this study than previous study possible due to the adoption of LC–MS/MS 2 . It is noteworthy that a great number of DEPs were located in mitochondria, implying the vital role of mitochondrial dysfunction in hypertension-related LVH.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Adult SHR is an ideal animal model of compensatory LVH, as supported by increased left ventricle relative mass, elevated left ventricular end-systolic pressure in combined with greater + dp/dt max in SHR. As expected, more DEPs were found in this study than previous study possible due to the adoption of LC–MS/MS 2 . It is noteworthy that a great number of DEPs were located in mitochondria, implying the vital role of mitochondrial dysfunction in hypertension-related LVH.…”
Section: Discussionsupporting
confidence: 79%
“…As a complicated pathological process, LVH may result from the changes of numerous proteins. Proteomics analysis is a potential approach to identify, characterize and quantify global changes in protein profile, and the approach has been applied to examine protein profiles in myocardium of spontaneously hypertensive rats (SHRs), an inbred homozygous rodent model of human essential hypertension 2 . However, the sample separation technologies used in previous studies are almost all two-dimensional polyacrylamide gel electrophoresis (2D PAGE).…”
Section: Introductionmentioning
confidence: 99%
“…HCM can be characterized by an increase in left ventricular myocardial mass. However, other causes of cardiac hypertrophy, such as hyperthyroidism, systemic hypertension, and aortic stenosis, are the primary differential diagnosis for this disease (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to participate in cellular regulation of apoptosis and proliferation, as well as the activation of transcription factors and protein degradation. It has been reported that hypertrophic stimulation can induce Hsp70 expression, which consequently causes cardiac dysfunction and the development of cardiac hypertrophy by activating JNK, p38-MAPK, Raf-1, and ERK (41). Studies have also revealed Hsp70 induction under conditions of different hypertrophic stress responses and subsequent activation of HDAC2 to trigger cardiac hypertrophy (42).…”
Section: Discussionmentioning
confidence: 99%